b(3+3b)-b(2b-3)=0

Simple and best practice solution for b(3+3b)-b(2b-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b(3+3b)-b(2b-3)=0 equation:



b(3+3b)-b(2b-3)=0
We add all the numbers together, and all the variables
b(3b+3)-b(2b-3)=0
We multiply parentheses
3b^2-2b^2+3b+3b=0
We add all the numbers together, and all the variables
b^2+6b=0
a = 1; b = 6; c = 0;
Δ = b2-4ac
Δ = 62-4·1·0
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$b_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$b_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{36}=6$
$b_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-6}{2*1}=\frac{-12}{2} =-6 $
$b_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+6}{2*1}=\frac{0}{2} =0 $

See similar equations:

| 3/7t+1/6=-4/7t-5/6 | | 4y2=12y | | 252=p+6(1-7p) | | y+×+150=180 | | 2x+24=4×-6 | | -6y+8y=-4+20 | | H(t)=-16t^2+93t | | 3/2=5/7x | | X-1/2=x/8 | | 8500=825+1535x | | X+(x*18)=380 | | X+(x*18)=360 | | 64^x=16^x-1 | | 6x-5=21+2x | | 3a-2/4=2 | | 6(x-7)=4x-4’ | | r²-3r-4=0 | | x-10=x+10/2 | | 1c-12=3c+12 | | Y=75+10y=50+15 | | {X+2y=15 | | 7/10+4/5x=5x | | 8(8n+14)=-16 | | -2(2+n)=10 | | -4(4n-7)=-4 | | 5(-2n-5)=25 | | 2(1n+6)=0 | | 7h=10=73 | | -5(-10+7n)=330 | | 5x+10=1+2 | | 7(-4-6n)=392 | | 5(10+6n)=-70 |

Equations solver categories